Developing a Curriculum for Non-Native Speakers of Arabic: Employing Thuaimah's Model as a Prototype - K. M. A. AHAMED ZUBAIR (RADINKA JAYA UTAMA PUBLISHER, 2024)
Teaching Arabic to non-native speakers faces various difficulties, such as curriculum design, environment, and other things. Attention should be focused on the design of suitable Arabic language teaching curricula for non-native speakers. Curricula are a vital component in the Arabic language for achieving academic objectives. The researcher aimed to understand the written texts as reflections of the author's ideas by describing and analyzing them. The researcher aimed to understand the written texts as reflections of the author's ideas by describing and analyzing them. This differs significantly between native and non-native speakers, requiring unique approaches for non-native speakers. The data, related to the curriculum concepts, are derived from Rushdi Ahmed Thuaimah's books using a documentation method. Thuaimah considered the curriculum as a system of interconnected elements. His teaching curriculum is based on philosophical foundations, namely behavioral, structural, pragmatic, and Islamic. These philosophies impact all the underlying foundations, such as linguistic, educational, psychological, and social foundations. The model for curriculum elements in teaching Arabic to non-native speakers by Thuaima consists of objectives, content, method, evaluation, and the teacher's guide. This indicates that the elements of the curriculum align and evolve based on expert input.